HUBUNGAN PENGETAHUAN DENGAN PERILAKU PERSONAL HYGIENE SISWA SAAT MENSTRUASI - Rahmawati, Lailatul; Laili, Ayik Nikmatul (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Adolescents are residents in the age group between the ages of 10 years and 18 years. During menstruation, teenagers need to know about reproductive organs, physical and psychological changes, in order to avoid risk factors that threaten the health and safety of reproductive organs. Hygiene during menstruation is important in determining the health of adolescent girls' reproductive organs. Prevention of diseases of the reproductive tract can be overcome if women are active in maintaining the cleanliness of their reproductive organs so that germs do not easily enter and cause infections. This research aims to determine the relationship between knowledge and students' personal hygiene behavior during menstruation. Analytical research method with a cross sectional design. Sampling used simple random sampling. research population 146, sample size 58. Questionnaire research instrument. Data analysis using the Kendall Tau test. The results of data analysis show a relationship between knowledge and personal hygiene behavior during menstruation at Trunojoyo Middle School with a P value of 0.039. The suggestion that researchers can convey is that there is a need for counseling and providing reproductive health education to students, both by teachers, health workers and parents, even though students already have fairly good knowledge, the aim is to reduce the incidence of disease due to students' lack of knowledge about personal hygiene during menstruation.